2022
DOI: 10.1111/cag.12740
|View full text |Cite
|
Sign up to set email alerts
|

Places of paid work and unpaid work: Caregiving and work‐from‐home during COVID‐19

Abstract: The home during COVID-19 has become a blended place, occupied by activities of care provision, paid work, and personal life.• This integrated landscape presents benefits to working carers such as increased flexibility, alongside challenges such as a lack of external carer supports. • These landscapes may continue in a post-COVID world, as organizations contemplate continuation of digital/hybridized workplaces and long-term care homes fall out of favour.Eldercare and places of eldercare have been radicalized wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…As a result, we anticipate that while reported presenteeism during working hours was high, this may not directly represent lost work. An earlier qualitative paper from this same workplace found that CEs were re-contracting their work hours outside of traditional working times, as remote working provides carers greater agency to negotiate their home, care and work responsibilities using a schedule that is most beneficial to them [ 31 ]. In this regard, we speculate that employees are still accomplishing the majority of their work tasks, albeit outside the usual 9–5 schedule due to work disruptions at home.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we anticipate that while reported presenteeism during working hours was high, this may not directly represent lost work. An earlier qualitative paper from this same workplace found that CEs were re-contracting their work hours outside of traditional working times, as remote working provides carers greater agency to negotiate their home, care and work responsibilities using a schedule that is most beneficial to them [ 31 ]. In this regard, we speculate that employees are still accomplishing the majority of their work tasks, albeit outside the usual 9–5 schedule due to work disruptions at home.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, caregivers may also have spent more time on caregiving tasks and, due to pandemic countermeasures, less formal caregiving may have been carried out. This may have had a negative effect on the caregiver burden [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants were also invited to review transcripts and modify their responses after transcription. The full description of the process of thematic analysis is described in a prior publication (Ding &Williams, 2022 ). Pseudonyms are used herein to protect the anonymity of participants.…”
Section: Methodsmentioning
confidence: 99%
“…This burden known to be both dynamic and bi-directional, with paid work impacting on caregiving and vice versa. From previous research, it was observed that when carer and worker roles conflict, paid work responsibilities often take priority over caregiving, regardless of carer-employees’ own preferences (Ding & Williams., 2022 ). This type of conflict, known generally as work-family conflict, is associated with decreased job satisfaction and increased job turnover, role stress, and burnout (Boles et al, 2001 ; Marks, 1998 ).…”
Section: Literature Reviewmentioning
confidence: 99%